AN ANALYSIS ON STUDENTS KNOWLEDGE CONSTRUCTION IN ONLINE DISCUSSION FORUM - Pratiwi Negara, Kartika Yoga Eka; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This study is to know the quality of students discussion indicated by messages posted in online discussion forum by looking at the distribution of students messages in term of task and not task-related. Majority of messages were Task-related category while the rest were Not Task-related category. Overlapped-coded message phenomenon which was found showed that students are able to think more complex in response to issues discussed. In the early stages of discussions, messages sent by the students tend to not task-related category which was caused by the lack of understanding about how to contribute properly; they tend to ask the technical issues and mutually encourage each other. In the middle until the end of the discussion, it showed the good trend that was proved with the students delivered opinions as well as the follow up questions, even accompanied by evidences and theories. It showed that students had been able to construct knowledge by contributing to the discussion, either in form of a simple or complex message. Keywords: Online Discussion Forum, Knowledge Construction Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui kualitas diskusi mahasiswa yang diindikasikan oleh pesan yang ada di forum diskusi online dengan melihat kontribusi mahasiswa dari segi kategoriTask dan Not Task. Sebagian besar pesan masuk ke dalam kategori Task-related sedangkan sisanya berada dalam kategori Not Task-related. Adanya fenomena overlapped-coded message yang ditemukan oleh penulis menunjukkan bahwa mahasiswa mampu untuk berpikir lebih kompleks. Pada tahap awal diskusi, pesan yang dikirim oleh mahasiswa cenderung ke kategori Not Task-related yang diakibatkan oleh kurang mengertinya mahasiswa tentang cara berkontribusi dengan baik; mereka cenderung bertanya tentang masalah teknis dan menyemangati satu sama lain. Di pertengahan sampai akhir diskusi, kualitas diskusi yang berlangsung cenderung meningkat karena mahasiswa mengemukakan pendapat dan pertanyaan lanjutan, bahkan disertai dengan bukti dan teori. Hal ini menunjukkan bahwa mahasiswa membangun pengetahuan baik dalam bentuk yang sederhana maupun kompleks. Kata kunci: Forum Diskusi Online, Pembangunan Pengetahuan